Modeling dependency in tourist arrivals to Thailand from China, Korea, and Japan using vine copulas - Ornanong Puarattanaarunkorn (2018)
Market interdependence has always been an interesting topic in the study of tourism demand. China, Japan, and Korea are important tourist markets for Thailand tourism. Understanding how the arrivals relate to each other can help in tourism management, in a way that it prepares the tourism industry to plan for the risk management of the tourism demand and tourism supply. The vine copula model was used to analyze the multiple dependencies by decomposing the diversity of the paircopulas which can be arranged and analyzed in a tree structure. For this study, both the C-vine copula and the D-vine copula were used to answer the research question. We give the same conditioning variable for both the C-vine and the D-vine copula models in order to find the answer to our question of whether these two models would give different results. The contributions of the study are obtained from the findings. The C-vine and D-vine copulas provided three pair-copulas, namely, China-Korea, China-Japan, and Korea-Japan given China and there exists a weak positive dependence in each pair. In addition, the results provide evidence that China has influence on the dependence between the tourist arrivals from Korea and Japan. Moreover, the three dimensions of the C-vine and D-vine copula models, which are given the same conditioning variable in the second tree, optimally provide the same estimates of the parameters of interest. © Springer International Publishing Switzerland 2014.